Risk Factors for Tracheobronchomalacia in Preterm Infants With Bronchopulmonary Dysplasia - Su, Ya-Ting; Chiu, Chun-Che; Lai, Shen-Hao; Hsia, Shao-Hsuan; Lin, Jainn-Jim; Chan, Oi-Wa; Chiu, Chih-Yung; Tseng, Pei-Ling; Lee, En-Pei (Frontiers in Pediatrics, 2021)
Aim: To identify the risk factors associated with the development of tracheobronchomalacia (TBM) in preterm infants with bronchopulmonary dysplasia (BPD). Optimal cutoff values for each risk factor were also determined. Methods: This was a retrospective cohort study using chart reviews of preterm infants at 36 week’s gestation or earlier, who underwent flexible fiberoptic bronchoscopy in a tertiary pediatric referral center between January 2015 and January 2020. Indications on the bronchoscopy examination included lobar atelectasis on the plain chest film, persistent CO2 retention, recurrent extubation failure for airway examination, or abnormal breathing sounds, such as wheeze, stridor, etc. Results: 58 preterm infants with BPD were eligible for enrollment in the study. TBM was identified in 29 (50%) patients. The gestational age and birth weight had no significant difference between two groups. The TBM group had significantly higher proportional of severe BPD compared with the group without TBM (68.9 v.s. 20.6%, p<0.001). Clinical parameters that were significantly different between infants with and without TBM were included in the multivariate analysis. Among these factors, severe BPD was the most powerful risk factor for the development of TBM in preterm infants with the odds ratio of 5.57 (1.32-23.5, p=0.019). The area under the receiver operating characteristic curve for PIP and the number of intubation days were 0.788 and 0.75, respectively. The best predictive power of PIP and the intubation days for TBM were 18.5 mmHg and 82 days. Conclusion: Preterm infants with severe BPD have the highest risk for the development of TBM. In addition, these preterm infants who receive higher PIP or are intubated for longer are at an increased risk of developing TBM. Bronchoscopy examination should be considered for early diagnosis and management of TBM in infants with these risk factors.